Pelaksanaan Pembelajaran Akidah Akhlak dalam Mengatasi Degradasi Moral - Farida Nabilah; Eli Masnawati (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The moral degradation that is currently occurring in the world of education needs special attention, because it is not only violence in verbal form but also in non-verbal form. The thin morals and manners possessed by students make it a difficult problem to overcome in the world of education. For this reason, the purpose of this study is to find out how learning aqidah and akhlak can shape morals and as an effort to overcome the existing moral degradation. The method in this study uses qualitative with a descriptive approach, while the data collection technique used interviews and observations. The results of the research that has been carried out, there is a gradual improvement in morals after learning and also implementing aqidah and akhlak in everyday life, especially at school.